Технологічні та експлуатаційні характеристики і параметри зубчастих передач евольвентного та синусоїдального зачеплення - Грицай, І. Є. (Видавництво Львівської політехніки, 2018)
Надійність машин великою мірою визначається якістю передач, які забезпечують їх функціонування. Найбільшого поширення набули евольвентні зубчасті передачі, проте вони мають істотні недоліки: шум на великих швидкостях, недостатня навантажувальна здатність, невисокі згинна міцність та опір циклічній втомі. Разом з тим, відома передача з вищими параметрами експлуатаційної якості без будь-яких змін у будові зубців коліс – це синусоїдальна передача. На основі розрахунків, наведених у статті, виведено залежності, якими аналітично описано геометричні та кінематичні параметри синусоїдальних передач, на основі яких розраховано сили в зачепленні, тертя в двох видах передач, зміну напружень в основі зубців. Показано, що синусоїдальна передача може бути як швидкісною, так і силовою, тобто вона є універсальною. Перспективним напрямом удосконалення синусоїдальних передач є виготовлення синусоїдальних коліс з асиметричними профілями зубців. Разом з тим, основною перевагою синусоїдальних коліс є простота технологія їх виготовлення – нарізання тонкими дисковими фрезами, встановленими ексцентрично зі збереженням кінематики фрезерування коліс черв’ячними фрезами.

The reliability of machines is largely determined by the quality of the transmissions that ensure their operation. The involute gear transmissions are the most widespread for today, despite the fact that they have significant disadvantages: high speed noise, insufficient load capacity, low bending strength and resistance to cyclic fatigue. However, higher parameters of operational quality without changes in its structure and without any modification of the teeth has a sinusoidal gear transmission. Based on the deduced dependencies and calculations, a number of geometry and kinematic transmission parameters of the sinusoidal gear transmission are calculated. This made it possible to calculate and compare forces in the engagement, friction in gear pars of two gear types, to investigate a changes in the stresses at the base of the teeth. So such a transmission can be both high-speed and power, that is, it is universal one. However the main advantage of sinusoidal gears and transmissions is the simplicity of their manufacturing technology – the cutting by thin disk mills, installed eccentrically while preserving the kinematics of standard hobs cutting – radial-circular manner of gears cutting: in cutting process cutter travels axially along the length of the gear tooth while the gear blank is rotated continuously. In practice its technology don’t required significant modernization of tool gear machine and could be widely applications.
Technological and operating characteristics and parameters of the effective transfer of the evolution and synusoidal loading
Keywords: зубчасті передачі; синусоїдальні колеса; експлуатаційні переваги; нова технологія; gears transmissions; sinusoidal gears transmission; quality; new gears technology; 621.9.02; 621.9.14